Effectiveness of virtual reality assisted active limb movement exercises for patients in the respiratory intensive care unit: a randomized pilot study - Jiani Wang; Chenxi Shi; Yanrui Jia; Qian Xiao (Journal of Rehabilitation Medicine)
Objective: The primary aim of this study is to compare the effectiveness of early active limb movement facilitated by virtual reality technologies with conventional exercise therapy in enhancing patient recovery in the Respiratory Intensive Care Unit. The follow-up period covers 1 week.